Benefit evaluation of sloping land conversion program in the upper reaches of the Yellow River - Zheng Guo; Shuhua Zhang; Zhi Zhang; Mingyu Xie (Heliyon)
This study used forestry statistical data and field survey data from 2000 to 2018 to analyze the ecological restoration effect of the returning farmland to forest project in the upper reaches of the Yellow River, considering four perspectives, namely, project construction goals, ecosystem quality, ecosystem service functions, and ecological restoration driving factors. One-way ANOVA and logit regression analysis methods were used for comparison. The results show that the implementation of the Grain for Green Project has reduced the carrying capacity of rural land, effectively curbed the continuous deterioration of the ecological environment, and protected and benefited the forest ecosystem. (1) Initiatives of the return farmland to forest project have achieved the expected goals, and the forest coverage rate has increased significantly from 5.26 % (in 2000) to 15.63 % (in 2019); the proportion of primary, secondary, and tertiary industries related to forestry has reached a reasonable level, and the economic benefits thereof continue to improve. (2) Indicators such as total forest and grass vegetation coverage, vegetation net primary productivity, and forest and grass health index reflect that the functional quality of the regional forest and grass ecosystem is gradually improving. (3) The ecosystem service function of the project region has improved considerably, and the ecological benefits are significant. (4) In terms of the contribution value of the driving forces for this ecological restoration project, they can be ranked as follows: government investment > reducing land carrying capacity > policy of returning farmland to forest > government management > hydrological factors > meteorological factors. (5) After the implementation of the Grain for Green Project, farmers' income has increased significantly, but the changes in livelihood capital income are not synchronized. As the ecological environment in the Grain for Green project areas gradually improved from deterioration, the natural capital and social capital of farmers' livelihood capital decreased significantly, while the physical capital and financial capital increased significantly, with no significant change in human capital. Farmers' satisfaction with the Grain for Green Project is as follows: natural capital has a significant negative impact, while financial capital and social capital have significant positive impacts, and there are no significant changes in physical capital and human capital. Finally, the consistency test results show that the fit is as high as 95 %, and the accuracy exceeds 90 %. Notably, the implementation of the Grain for Green Project has played a pivotal role in ecological restoration and contributed greatly to ecological benefits. These achievements provide a scientific basis and theoretical support for the country to formulate relevant policies for forestry projects, which holds great significance for the country in addressing the contradiction between economic and social development and ecological protection.